Dynamics of Organizational Populations: Density, Legitimation, and CompetitionDynamics of Organizational Populations: Density, Legitimation, and Competition by Hannan Michael T. Carroll Glenn R.. New York: Oxford University Press, 1992, 278 pp. - Miner, Anne S. (Academy of Management Review, 1993)
The article reviews the book ?Dynamics of Organizational Populations: Density, Legitimacy and Competition,? by Michael T. Hannan and Glen R. Carroll.